The importance of online customer management service done by digital marketing agency Asiatic mindshare limited to change the landscape of marketing in Bangladesh - Rahman, Maksudur (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.